Adult Bilateral Ureteroceles Presenting with Lower Urinary Tract Symptoms and Acute Urinary Retention. (26th June 2018) - Rompré-Brodeur, Alexis; Andonian, Sero
Abstract : Ureterocele is a well-known pathologic entity in the pediatric urology population but remains a diagnostic and treatment challenge in the adult population. Adult ureteroceles remain a diagnostic challenge for the adult urologist. Its prevalence is estimated between 1/500 and 1/4000 patients with a wide variety of clinical presentations. We present the case of a 30-year-old female patient who presented with severe lower urinary tract symptoms (LUTS) and acute urinary retention secondary to prolapsing bilateral single-system orthotopic ureteroceles. She was successfully treated with transurethral unroofing of her bilateral ureteroceles and she is currently asymptomatic. This case represents the first reported case of bilateral ureteroceles presenting with severe LUTS and subsequent urinary retention from the prolapse of one of the ureteroceles. We provide a review of the most recent case series of adult ureteroceles and their outcomes. Transurethral unroofing of the ureterocele is a safe and minimally invasive approach for this disease.